การใช้สารอินทรีย์เป็นตัวเร่งเชิงแสงในการสังเคราะห์อนุพันธ์ซัลไฟด์จากเกลือไดอะโซเนียม - อินทัช สายเชื้อ (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
Typically, diazonium compounds were used as starting materials for coupling reactions in the presence of metal catalyst at high temperature. To improve such processes, we aim to develop a diazonium coupling reaction using Rose Bengal as a photocatalyst under visible light irradiation. In this work, three diazonium 1a, 2a and 3a were synthesized in 31-52% yields and used as the starting materials to prepare 1) asymmetrical thioether 2) acetamide and 3) symmetrical thioether in the presence of Rose Bengal as a photocatalyst. For the synthesis of asymmetrical thioether, the reaction between diazonium 2a and 2-mercaptopyridine (b) gave the desired asymmetrical thioether 2b in 44% yield using 5% Rose Bengal as a catalyst under white LED irradiation. Next, acetamide compounds 2c and 3c were prepared from diazonium 2a and 3a respectively. The reaction was conducted in acetonitrile and irradiated by white LED. The acetamide 2c and 3c were obtained in moderate yields. Finally, we successfully prepared symmetrical thioether 2d from diazonium 2a and sodiumsulfide nonahydrate as sulfur source catalyzed by Rose Bengal. Under the optimized condition, the result shown that the use of mixed solvent (THF: water, (1:1)) gave the desired product 2d in 18% yield.